2004
DOI: 10.1023/b:ddas.0000034567.53748.df
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Limitations of Sirolimus Conversion in Liver Transplant Patients Who Develop Renal Dysfunction on Calcineurin Inhibitors

Abstract: This study evaluates sirolimus in preserving renal function in 28 patients who developed renal insufficiency after liver transplantation. Patients with a creatinine level higher than 1.8 mg/ml were eligible for conversion. Of the 28 patients, 7 (25%) did not tolerate sirolimus, 6 (21%) progressed to end-stage renal disease (ESRD), and 14 (50%) have been maintained on sirolimus with stable renal function. The 28 patients overall had a decline in creatinine of 0.38 mg/dl (P = 0.029) at week 4, with a small incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
2
20
0
1
Order By: Relevance
“…Dyslipidemia was reported in up to 44% of patients. 12,47,48 In 4 of our patients, slight adverse effects (thrombocytopenia, gingival hyperplasia, oral ulceration) occurred. Only 1 patient had to have sirolimus therapy withdrawn because of acneiform rash, and treatment was converted to everolimus.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Dyslipidemia was reported in up to 44% of patients. 12,47,48 In 4 of our patients, slight adverse effects (thrombocytopenia, gingival hyperplasia, oral ulceration) occurred. Only 1 patient had to have sirolimus therapy withdrawn because of acneiform rash, and treatment was converted to everolimus.…”
Section: Discussionmentioning
confidence: 72%
“…[12][13][14] Unfortunately, the follow-up of most of the studies was relatively short, often less than 12 months. Therefore, it is uncertain if the initial increase in creatinine clearance will be sustained over a longer time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, sirolimus conversion should be initiated early since late conversion rarely improves chronic renal dysfunction [49] . In fact, several studies have shown that in patients with preexisting renal disease, sirolimus can worsen nephrotoxicity and promote proteinuria [5052] .…”
Section: Mtor Inhibitorsmentioning
confidence: 99%
“…Sirolimus can limit or even avoid the adverse effects of calcineurin inhibitors and simultaneously guarantee adequate immunosuppression. [3][4][5][6] There are 2 regimens for converting to sirolimus from calcineurin inhibitors in liver transplant. 5 One is partial conversion by combining low-dose sirolimus with reduced calcineurin inhibitors, which was used in most studies of the early trials.…”
Section: Discussionmentioning
confidence: 99%